STRATEGI PENYEDIAAN BENIH BAWANG MERAH LEMBAH PALU DI DESA BULUPOUNTU JAYA KECAMATAN BIROMARU KABUPATEN SIGI - Max Nur Alam (Universitas Tadulako, 2011)
The aims of the research were to determine the income level of local Palu shallot seed provider business and to determine the strategy of the business in Palu Valley. The research population was four local Palu shallot seed provider business groups taken from Bulupountu Jaya of Biromaru Sub District Sigi Regency. Each group was represented by four people; the group leader and its three members. Therefore the number of samples included as the research respondents were 16 people. The data were analyzed using income and SWOT analyses. The research results showed that the average of farmers’ income from the shallot seed business was IDR 84.355.000 ha-1planting season-1. The SWOT matrix on the formulation of strategy for the local Palu shallot seed business indicated “SO strategy”.